105 Effect of a Yeast Product on Palatability, Fecal Microbiota, and Blood Values of Adult Cats. (21st September 2022) - Lin, Ching-Yen; Panasevich, Matthew; Daristotle, Leighann; Frantz, Nolan
Abstract: Yeast products have been fed to livestock for their benefits of modulating immune responses, enhancing gut health, and improving production. Although studies investigating the effects of yeast in companion animals have emerged in recent years, research on cats is still lacking. Therefore, these studies evaluated the effects of a Saccharomyces cerevisiae fermentation product (SCFP) on diet palatability and digestibility, fecal microbiota, and blood values in adult cats. Twelve adult cats (mean BW=4.02 kg, mean age=3.4 y) were used in a cross-over design with two 28-day feeding periods and a 14-day washout between feeding periods. Cats were randomly assigned to a control dry kibble diet or a diet containing 1, 380 ppm SCFP. Fecal samples were collected during days 22 to 27 for measurements of nutrient digestibility, stool quality, and fecal microbiome. On day 28, urine samples were collected for pH measurement and blood samples were collected for serum chemistry and complete blood count analyses. A separate standard 2-day palatability test was conducted using 30 cats fed the control and SCFP diets. Protocols were approved by the Institutional Animal Care and Use Committee before studies commenced. All data were analyzed using Mixed Models procedure of SAS (v9.4). Nutrient digestibility, stool quality, and urine pH were not altered by SCFP. Blood values were all within the reference ranges. Serum cholesterol concentrations increased (P< 0.05) and monocyte percentage tended to increase (P< 0.10) when cats consumed SCFP. When consuming SCFP, cats had decreased (P< 0.05) relative abundances of Sutterella and Paraprevotella from the sequencing results and tended to have greater (P< 0.10) Bifidobacterium spp. from the PCR results. The SCFP diet had better palatability, with an intake ratio of 0.69: 0.31 (vs. control). Results of these studies suggest that SCFP is safe for cat consumption and palatable, and by altering intestinal microbial populations, may promote gut health.